Urrets-Zavalia syndrome following implantable collamer lens (ICL) implantation: a case report and review of the literature - Ke Li; Ting Huang; Juan Yuan; Siyi Bao (Journal of Medical Case Reports)
Abstract Background Urrets-Zavalia syndrome is a condition that arises after eye surgery, often linked to increased intraocular pressure following the procedure. We present a case of a progressively dilated and fixed pupil in one eye following the implantation of a toric implantable collamer lens. There are no documented cases in the literature regarding this condition in China. The patient gradually and completely recovered after our intervention. This case differs from all previous implantable collamer lens implantation cases, and the treatment method used is unprecedented. Case presentation A 33-year-old Han Chinese woman successfully had a toric implantable collamer lens implanted in both eyes. The left eye surgery was performed on the first day. Within 10 days post-operation, the pupil of the left eye continued to dilate. We considered the cause of pupil dilation in this case to be pupillary sphincter paralysis caused by elevated intraocular pressure and the excessive size of the toric implantable collamer lens. Therefore, the toric implantable collamer lens needed to be replaced with a smaller one. However, it would take 3–4 months to prepare the new toric implantable collamer lens. After discussing the situation with the patient and obtaining her consent, we repositioned the toric implantable collamer lens to the new target location. The alternative toric implantable collamer lens was ultimately available more than 2 months later. After the replacement operation, the pupil gradually returned to normal. Conclusion The vault is not the only criterion for determining whether the size of an implantable collamer lens is appropriate. In this case, it can be concluded that the potential reason for pupil dilation was that the size of the toric implantable collamer lens was too large, and it reversed after changing to a smaller size. The dilated pupil would not return to normal if the toric implantable collamer lens were not replaced. When persistent mydriasis (Urrets-Zavalia syndrome) occurs after implantable collamer lens implantation, it is essential to determine whether the implantable collamer lens size is appropriate besides controlling the intraocular pressure. In addition, alternative toric implantable collamer lenses often need to be customized. During long waiting times, provisional implantable collamer lens realignment will predictive simulation for planned exchange.